Dirāsah Tahlīliyah Liltadrībāt Fī Kitāb Ta’lim Allughah Al’arabiyah Litulāb Alshafi Alkhāmis Al Ibtidāī Liwizārah Alsyu`ūn Aldīniyah Al Indūnīsiyah ām 2020 - Ardinil Yulianda; Fajar Sidiq; Hisan Mursalin (Ukazh: Journal of Arabic Studies, 2022)
This study aimed to know the forms and types of exercises prepared in the Arabic language teaching book for the fifth grade of primary school of the Indonesian Ministry of Religious Affairs in 2020, and this study follows the analytical descriptive approach, and the method used by the researcher in collecting data is the library method and the documentary method. The result of this research is that the form of exercises in the Arabic language teaching book for the fifth grade of primary school of the Indonesian Ministry of Religious Affairs in 2020 AD is divided into the four language skills: listening, speaking, reading, writing, including: optional, pairing, transferring, exchanging question and answer, arranging Random letters, true and false. Penelitian ini bertujuan untuk mengetahui bentuk dan jenis latihan yang disusun dalam buku ajar bahasa Arab kelas V SD Kementerian Agama RI Tahun 2020. dan metode yang digunakan peneliti dalam mengumpulkan data. adalah metode perpustakaan dan metode dokumenter. Hasil dari penelitian ini adalah bentuk latihan dalam buku ajar bahasa Arab untuk kelas V SD Kementerian Agama RI Tahun 2020 M terbagi menjadi empat keterampilan berbahasa yaitu menyimak, berbicara, membaca, menulis, meliputi: pilihan, memasangkan, mentransfer, bertukar tanya jawab, menyusun huruf Acak, benar dan salah. هدفت هذه الدراسة إلى معرفة أشكال و أنواع التدريبات المعدة في كتاب تعليم اللغة العربية للصف الخامس الابتدائي لوزارة الشؤون الدينية الإندونيسية عام 2020، وهذه الدراسة تسلك على منهج الوصف التحليلي وأما الطريقة يستخدمها الباحث في جمع البيانات هي الطريقة المكتبية و الطريقة الوثائقية. ونتيجة هذا البحث هي أن شكل التدريبات في كتاب تعليم اللغة العربية للصف الخامس الابتدائي لوزارة الشؤون الدينية الإندونيسية عام 2020 م مقسم إلى المهارات اللغوية الأربعة: الاستماع، والكلام، والقراءة، الكتابة، منها : الاختياري، والتزويج، والتحويل، وتبادل السؤال و الجواب، وترتيب الحروف العشوائية، والصواب و الخطاء